2016
DOI: 10.1002/ece3.2498
|View full text |Cite
|
Sign up to set email alerts
|

Intragenomic conflict produces sex ratio dynamics that favor maternal sex ratio distorters

Abstract: Maternal sex ratio distorters (MSDs) are selfish elements that enhance their transmission by biasing their host's sex allocation in favor of females. While previous models have predicted that the female‐biased populations resulting from sex ratio distortion can benefit from enhanced productivity, these models neglect Fisherian selection for nuclear suppressors, an unrealistic assumption in most systems. We used individual‐based computer simulation modeling to explore the intragenomic conflict between sex ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…Variation in the secondary sex ratio biases (among flowering plants) between species has been attributed to sexual dimorphism in reproductive cost, for example, the high incidence of female bias in wind-pollinated species is interpreted as a result of higher reproductive costs in males leading to higher male mortality (Field et al, 2013). However, female-biased population sex ratios in seeds (primary sex ratio), and also variation in sex ratio between families, as reported here, are also consistent with entirely different mechanisms, such as meiotic drive and cyto-nuclear interactions (Rood & Freedberg, 2016; Unckless & Clark, 2014). These mechanisms arise from genetic conflict and can confer reproductive advantage in colonizing species (Rood & Freedberg, 2016; Unckless & Clark, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Variation in the secondary sex ratio biases (among flowering plants) between species has been attributed to sexual dimorphism in reproductive cost, for example, the high incidence of female bias in wind-pollinated species is interpreted as a result of higher reproductive costs in males leading to higher male mortality (Field et al, 2013). However, female-biased population sex ratios in seeds (primary sex ratio), and also variation in sex ratio between families, as reported here, are also consistent with entirely different mechanisms, such as meiotic drive and cyto-nuclear interactions (Rood & Freedberg, 2016; Unckless & Clark, 2014). These mechanisms arise from genetic conflict and can confer reproductive advantage in colonizing species (Rood & Freedberg, 2016; Unckless & Clark, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…The sex ratio influences the sexual selection and is an important parameter in the evolution of a species (Janicke & Morrow, 2018). It also plays an essential role in the demography, mating system, and genetics of a population, and can influence its evolutionary trajectory (Freedberg & Taylor, 2007; Hartl et al, 1997; Rood & Freedberg, 2016; Sowersby et al, 2020). According to Fisher's principle (Fisher, 1930), frequency‐dependent selection maintains a balanced sex ratio in most populations.…”
Section: Introductionmentioning
confidence: 99%
“…These vertically-transmitted infections cause little pathogenicity to their hosts [10,23,28,29], even having beneficial effects in G. roeselii [23]. Because of female excess and positive effect on fitness-related traits, host populations infected with the feminizing N. granulosis strains are predicted to have higher growth rate and may help the invasive host G. roeselii in colonizing new territories [30]. Supporting this hypothesis, Quiles et al [31] found that the feminizing N. granulosis strain of G. roeselii is associated with the only one host mitochondrial genotype that invaded Western Europe after the last glaciation [32].…”
Section: Introductionmentioning
confidence: 99%